Molecular detection of β-lactamase and integron genes in clinical strains of Klebsiella pneumoniae by multiplex polymerase chain reaction - Mansour Sedighi; Masoumeh Halajzadeh; Rashid Ramazanzadeh; Noor Amirmozafari; Mohsen Heidary; Serve Pirouzi (Revista da Sociedade Brasileira de Medicina Tropical)
Abstract INTRODUCTION: Infections caused by β-lactamase-producing gram-negative bacteria, such as Klebsiella pneumoniae, are increasing globally with high morbidity and mortality. The aim of the current study was to determine antimicrobial susceptibility patterns and the prevalence of antibiotic resistance genes (β-lactamase and integron genes) using multiplex PCR. METHODS One-hundred K. pneumoniae isolates were collected from different clinical samples. Antibiotic susceptibility testing was performed with thirteen different antibiotics. Multiplex-PCR was used to detect β-lactamase (bla TEM, bla CTX-M, bla SHV , bla VEB, bla PER, bla GES, bla VIM, bla IMP, bla OXA, and bla KPC) and integron genes (int I, int II, and int III). RESULTS: The highest and lowest rate of resistance was exhibited against amikacin (93%) and imipenem (8%), respectively. The frequency of β-lactamase-positive K. pneumoniae was 37%, and the prevalence of the bla TEM, bla CTX-M, bla SHV , bla VEB, bla PER, bla GES, bla VIM, bla IMP, bla OXA, and bla KPC genes was 38%, 24%, 19%, 12%, 6%, 11%, 33%, 0%, 28%, and 23%, respectively. Of the 100 isolates, eight (8%) were positive for class I integrons; however, class II and III integrons were not detected in any of the strains. CONCLUSIONS: These results indicate co-carriage of a number of β-lactamase genes and antibiotic resistance integrons on the same plasmids harboring multi-drug resistance genes. It seems that these properties help to decrease treatment complications due to resistant bacterial infections by rapid detection, infection-control programs and prevention of transmission of drug resistance.